2014
DOI: 10.1002/asia.201402739
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochromic Luminescence Characteristics of Pyridine‐Terminated Chromophores in the Solid State and in a Poly(vinyl alcohol) Matrix

Abstract: Mechanoresponsive luminophores containing different substituted pyridine rings at the molecular terminus are synthesized and their photoluminescence properties are investigated. The solid chromophore with a 4-substituted pyridine ring exhibits a reversible photoluminescent color change, while the 2-substituted chromophore shows only a small change in luminescence, and the 3-substituted chromophore displays an irreversible photoluminescent color change with mechanical grinding. A change of the sample color in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The luminescentp roperties of organicf luorophores in the solid state can be occasionally affected by molecular distributions and morphology.W hen luminescent chromism was induced by mechanical stimuli, such as pressing,c rushing, and grinding,t hese molecules are classified as mechanoluminescent chromic (MLC) compounds. [1][2][3][4][5][6][7] Because of the potential versatility of MLC materials, such as for optical recording/ memory devices, [8] pressure indicators, [9] stress detectors with polymers, [10] and bioprobes for monitoring microenvironmental changes, [11,12] not only the development of MLC compounds, but also modulation of luminescent properties, such as color, intensity,a nd chromism direction,are hot topics with high relevance.H owever,b ecause most conventional luminescent dyes intrinsically show weake mission in the solid state due to aggregation-causedq uenching (ACQ), there are limited numbers of molecular skeletons with clear MLC behavior.I ndeed, it is still challengingt op recisely regulate MLC properties according to preprogrammed design.O ne of the promising candidates to produce MLC compounds with functional tunability is the class of aggregation-inducede mission [13][14][15][16][17][18][19][20] (AIE)-active molecules, which can show bright emission only in the aggregated state. [21] In particular, recent studies reported that vari-ous types of solid-state fluorescent materials with stimuliresponsive fluorescentc hromism involving MLC could be prepared based on the regulation of electronic conjugation through AIE-active organoboron complexes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The luminescentp roperties of organicf luorophores in the solid state can be occasionally affected by molecular distributions and morphology.W hen luminescent chromism was induced by mechanical stimuli, such as pressing,c rushing, and grinding,t hese molecules are classified as mechanoluminescent chromic (MLC) compounds. [1][2][3][4][5][6][7] Because of the potential versatility of MLC materials, such as for optical recording/ memory devices, [8] pressure indicators, [9] stress detectors with polymers, [10] and bioprobes for monitoring microenvironmental changes, [11,12] not only the development of MLC compounds, but also modulation of luminescent properties, such as color, intensity,a nd chromism direction,are hot topics with high relevance.H owever,b ecause most conventional luminescent dyes intrinsically show weake mission in the solid state due to aggregation-causedq uenching (ACQ), there are limited numbers of molecular skeletons with clear MLC behavior.I ndeed, it is still challengingt op recisely regulate MLC properties according to preprogrammed design.O ne of the promising candidates to produce MLC compounds with functional tunability is the class of aggregation-inducede mission [13][14][15][16][17][18][19][20] (AIE)-active molecules, which can show bright emission only in the aggregated state. [21] In particular, recent studies reported that vari-ous types of solid-state fluorescent materials with stimuliresponsive fluorescentc hromism involving MLC could be prepared based on the regulation of electronic conjugation through AIE-active organoboron complexes.…”
Section: Introductionmentioning
confidence: 99%
“…When luminescent chromism was induced by mechanical stimuli, such as pressing, crushing, and grinding, these molecules are classified as mechanoluminescent chromic (MLC) compounds . Because of the potential versatility of MLC materials, such as for optical recording/memory devices, pressure indicators, stress detectors with polymers, and bioprobes for monitoring microenvironmental changes, not only the development of MLC compounds, but also modulation of luminescent properties, such as color, intensity, and chromism direction, are hot topics with high relevance. However, because most conventional luminescent dyes intrinsically show weak emission in the solid state due to aggregation‐caused quenching (ACQ), there are limited numbers of molecular skeletons with clear MLC behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of 5 : A mixture of 4‐bromophenylacetonitrile (1.5 g, 7.7 mmol) and 4‐pyridine carboxyaldehyde (0.84 g, 6.4 mmol) was dissolved in 12 mL of methanol. Potassium tert‐butoxide (0.18 g, 1.6 mmol) dissolved in 4 mL of methanol was added dropwise to this solution with stirring, and the reaction mixture was stirred at room temperature for 4 h. The crude product was removed by filtration and recrystallized from methanol to give 1.8 g of 5 as white, needle‐like crystals (mp 188–193 °C) in 94% yield.…”
Section: Methodsmentioning
confidence: 99%
“…The compounds contained a pyridine terminal and exhibited a red shift in the diffuse reflectance spectrum and photoluminescence color upon mechanical grinding. In addition, the PL color of the ground powder was further red shifted upon fuming to acid vapor . Recently, we demonstrated MCL behavior in a hydrogen‐bonded complex consisting of a pyridine‐terminated MCL compound and a mechano‐inactive acidic dopant .…”
Section: Introductionmentioning
confidence: 97%